Satisfaction with opioid prescription and use after minor gynaecologic surgery: a pilot prospective study - Chailee Moss; Carolyn Brookhart; Prerna Pandya; Mostafa A. Borahay; Melindia Mann; Victoria Handa; Anna Maya Powell (Taylor & Francis Group, 2023)
To describe predictors of patient satisfaction with pain control including opioid prescribing practices, patients undergoing minor gynaecologic and urogynaecologic surgeries were included in a prospective cohort study. Satisfaction with postoperative pain control by opioid prescription status was analysed using bivariate analysis and multivariable logistic regression, controlling for potential confounders. Among participants completing both postoperative surveys, 112/141 (79.4%) reported pain control satisfaction by day 1-2 and 118/137 (86.1%) by day 14. While we were underpowered to detect a true difference in satisfaction by opioid prescription, there were no differences in opioid prescription among patients satisfied with pain control [52% vs. 60% (p = .43) among satisfied patients at day 1-2 and 58.5% vs. 37% (p = .08) at day 14]. Significant predictors of pain control satisfaction were postoperative day (POD) 1-2 average pain at rest [aOR 0.72 (95% CI 0.52-0.99), p = .04], rating of shared decision-making [aOR 1.16 (95% CI 1.004-1.34), p = .04], amount of pain relief [aOR 1.28 (95% CI 1.07-1.54), p = .008) and POD 14 shared decision-making rating [aOR 1.45 (95% CI 1.19-1.77), p = .002].Impact Statement What is already known on this subject? There are little data published on opioid prescription rates after minor gynaecologic procedures and no formal evidence-based guidance for gynaecologic providers for opioid prescribing. Few publications describe rates of opioid prescription and use following minor gynaecologic procedures. In the setting of a dramatic escalation of opioid misuse in the United States over the last decade, we sought to describe our practice of opioid prescription following minor gynaecologic procedures and answer the question of whether patient satisfaction is affected by opioid prescription, fill and use. What do the results of this study add? Though underpowered to detect our primary outcome, our results suggest that patient satisfaction with pain control may primarily be significantly affected by the patient's subjective assessment of shared decision-making with the gynaecologist. What are the implications of these findings for clinical practice and/or further research? Ultimately, these preliminary findings suggest a larger cohort is needed to answer the question of whether pain control satisfaction is influenced by receipt/fill/use of opioids after minor gynaecologic surgery.